Optimizing Infak Funds in Efforts to Empower Nutrition of Marginalized Communities - Azizah, Luthfiah; Juvither Teguh Alfharizqi, Mochammad (El-kahfi | Jurnal Ekonomi Islam, 2025)
Malnutrition and stunting remain persistent challenges in Indonesia and other Muslim-majority countries, demanding innovative financing approaches that address both immediate and structural needs. This study examines the role of infaq as an Islamic social finance instrument in supporting nutritional empowerment for marginalized communities. Employing a systematic literature review of 32 studies published between 2015 and 2025 across Scopus, Web of Science, and national SINTA databases, the analysis followed PRISMA 2020 guidelines to ensure transparency in study selection and synthesis. The review identified five major themes: governance and accountability, digitalization of philanthropy, community-based empowerment, hybrid consumptive–productive models, and alignment with the Sustainable Development Goals. Evidence from randomized and quasi-experimental studies demonstrated that targeted interventions, such as supplemental feeding and maternal education, improve short-term nutritional outcomes, while integrated and well-governed models strengthen long-term resilience. Despite these promising insights, rigorous evaluations directly linking infaq allocation to nutritional indicators remain limited, underscoring the need for pre-registered trials, digital fund-tracking, and stronger institutional collaborations. By synthesizing empirical findings with Islamic economic principles and the maqasid al-shariah, this study proposes a conceptual framework positioning infaq not only as a charitable mechanism but also as a developmental instrument that bridges global health agendas with the ethical imperatives of Islamic economics